2001
DOI: 10.1093/oxfordjournals.jbchem.a003028
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Studies of Escherichia coli Biotin Synthase via a Chemical Modification and Site-Directed Mutagenesis Approach

Abstract: In Escherichia coli, biotin synthase (bioB gene product) catalyzes the key step in the biotin biosynthetic pathway, converting dethiobiotin (DTB) to biotin. Previous studies have demonstrated that BioB is a homodimer and that each monomer contains an iron-sulfur cluster. The purified BioB protein, however, does not catalyze the formation of biotin in a conventional fashion. The sulfur atom in the iron-sulfur cluster or from the cysteine residues in BioB have been suggested to act as the sulfur donor to form th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, when the enzyme returns to reductive anaerobic conditions, iron and sulfide are mobilized to regenerate a (4Fe−4S) cluster. ,, The active enzyme form is the one containing the (4Fe−4S) cluster. Site-directed mutants of BioB in which the cysteines of the conserved sequence (Cys53, Cys57, Cys60) have been changed into alanine are inactive. It has been reported that under certain reconstitution conditions each polypeptide can carry two clusters, one (4Fe−4S) cluster chelated by the cysteine triad and a (2Fe−2S) cluster presumably bound to three other conserved cysteines, Cys97, Cys128, and Cys188. The presence of two different clusters in different sites in this type of enzyme preparation has been recently demonstrated by Mössbauer spectroscopy using differently substituted 57 Fe protein . The cluster composition of BioB is, however, not yet firmly established.…”
Section: Biosynthesis Of Biotin: the Biotin Synthasementioning
confidence: 98%
See 3 more Smart Citations
“…However, when the enzyme returns to reductive anaerobic conditions, iron and sulfide are mobilized to regenerate a (4Fe−4S) cluster. ,, The active enzyme form is the one containing the (4Fe−4S) cluster. Site-directed mutants of BioB in which the cysteines of the conserved sequence (Cys53, Cys57, Cys60) have been changed into alanine are inactive. It has been reported that under certain reconstitution conditions each polypeptide can carry two clusters, one (4Fe−4S) cluster chelated by the cysteine triad and a (2Fe−2S) cluster presumably bound to three other conserved cysteines, Cys97, Cys128, and Cys188. The presence of two different clusters in different sites in this type of enzyme preparation has been recently demonstrated by Mössbauer spectroscopy using differently substituted 57 Fe protein . The cluster composition of BioB is, however, not yet firmly established.…”
Section: Biosynthesis Of Biotin: the Biotin Synthasementioning
confidence: 98%
“…52,53 It is a homodimer of 77 kDa, with each polypeptide chain carrying an oxygensensitive (4Fe-4S) cluster, probably ligated by three cysteines of a CXXXCXXC box conserved among all BioB known sequences and a fourth still not identi- fied ligand. [54][55][56][57][58][59][60] In the presence of oxygen, the iron center is unstable and loses iron and sulfide, being converted into a (2Fe-2S) cluster. However, when the enzyme returns to reductive anaerobic conditions, iron and sulfide are mobilized to regenerate a (4Fe-4S) cluster.…”
Section: Biosynthesis Of Biotin: the Biotin Synthasementioning
confidence: 99%
See 2 more Smart Citations
“…Metal Identification-1,10-Phenanthroline was used to determine the iron content of a protein (20,21 and has a maximal absorbance at 510 nm. Each of the ADHs (3-5 M final concentration) was mixed with 1,10-phenanthroline (1.5-2 mM final concentration) and incubated at 4°C until the activity was completely abolished (usually 1-2 h).…”
mentioning
confidence: 99%